INOVATION OF ISLAMIC HOLISTIC MIDWIFERY CARE DOCUMENTATION DIGITAL-BASED AS A LEARNING MEDIA FOR UNDERGRADUATE MIDIWFERY STUDENTS ‘AISYIYAH BANDUNG UNIVERITY - Annisa Ridlayanti; Astuti Suryad; Dhiva Adzkia Iskandar (UNIVERSITAS AIRLANGGA, 2023)
Abstract The era of the industrial revolution 5.0 demands that information technology systems can be utilized in recording and reporting midwifery care. This is intended to facilitate the achievement of the goal of documenting midwifery care. This study aims to design SOAP Digital as a learning medium and find out the use of digital SOAP innovation. This study used an experimental approach post test only control group design. Researchers made a pilot project to design and build innovations documenting digital-based Islamic holistic midwifery care. Digital SOAP operation technology interventions are carried out on the object of study. After that, an evaluation or feed back is given through the G-form on the object. The object of this study is a bachelor of midwifery student of FIKes Unisa Bandung. The results of data collection were analyzed using spss for windows software. The results showed that the digital-based Islamic holistic midwifery documentation application has 2 versions, namely the web version and the android version. This software installation has a capacity of 500 MB and requires less than 1GB of storage. The advantages of designing digital SOAP application innovations are that they are more effective in time (87%), more efficient in using paper (92%), more modern because they can use a PC, laptop, or smartphone (92%), more practical (87%), minimal risk of damaged or lost data (95%), and long data storage (90%). The results of the Spearman rho correlation data analysis test showed p-value of 0.000 < 0.05 so that it can be concluded that there is a correlation between the advantages of digital SOAP applications and student satisfaction.